Faktor Risiko Kejadian Stunting pada Balita di Negara Berkembang - Qurratu Falmuariat; Thresya Febrianti; Mustakim Mustakim (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction; Stunting in toddlers is one of the nutritional problems in the world, especially in developing countries. As many as 21.3% or around 144 million toddlers in the world are stunted, more than half of the world's stunted toddlers are from Asia, and more than two-fifths live in Africa. Stunting is a serious threat to the existence of children as the next generation of a nation. Purpose; This study analyzed the risk factors associated with the incidence of stunting in toddlers in developing countries using a systematic literature review and meta-analysis. Method; Literature search using online journal portals namely ProQuest, PubMed, and Garuda. The journal used in this study is a journal with a maximum reputation of Q2 and sinta 2, in the period 2010-2020, with a cross-sectional and case-control study design. Results; Based on the search results, seven kinds of literature were obtained, and conducted by systematic literature review was. Conclusion; The results of the meta-analysis of risk factors related to the incidence of stunting in toddlers in developing countries are birth weight and exclusive breastfeeding